Examining the Relationships between the Burnout Levels and Creative Thinking Levels of Special Education Teachers - Gazelci, Rabia Sultan; Güven, Didem; Ogelman, Hülya Gülay (Muhammed ZİNCİRLİ, 2022)
In this study, the relationships between the burnout and creative thinking levels of special education teachers (SET) were examined. In line with this purpose, 214 special education teachers were reached. Maslach Burnout Inventory-Educator’s Survey and Marmara Creative Thinking Tendency Scale were used in the study. As a result of the screening conducted based on the purpose, it was revealed that the creative thinking tendencies of SETs decrease as their burnout levels increase; their creative thinking, self-discipline, novelty-seeking, courage, curiosity, and flexibility levels decrease as their emotional exhaustion levels increase; and their creative thinking, self-discipline, novelty-seeking, courage, curiosity, doubt, and flexibility levels increase as their personal accomplishment levels increase. In conclusion, improving the salaries, providing trainings on scientific-based practices, and organizing in-service trainings were suggested in the study in order to reduce the burnout of SETs and increase their creative thinking tendencies.
Keywords: Special education teachers; Creative thinking; Occupational burnout